Effect of different atmospheric and subatmospheric cooking techniques on qualitative properties and microstructure of artichoke heads. (November 2020) - Rinaldi, Massimiliano; Littardi, Paola; Cavazza, Antonella; Santi, Saverio; Grimaldi, Maria; Rodolfi, Margherita; Ganino, Tommaso; Chiavaro, Emma
Graphical abstract: Highlights: Boiling and steaming deeply modified the microstructure. Steaming gave the best results for the nutritional quality. Vacuum cooking maintained good colour and texture. Sous-vide cooking presented the highest content of HMF. Abstract: Quartered Violetto artichokes were cooked with different treatments (boiling, steaming, sous vide and vacuum cooking) at the same cooking value at the thermal centre. Then, the physical (moisture content, texture and colour), histological and chemical (phenolic, 5-hydroxymethylfurfural (HMF) and furan content, total antioxidant capacity) features of bracts and hearts were assessed. A deeply modified microstructure was observed in boiled and steamed samples with an evident decrease in hardness both for bracts and hearts. Lightness of two anatomical parts was decreased by all the treatments (with the exception of sous vide bracts). The highest total colour difference was recorded for steamed samples, whereas the lowest was noted for sous vide samples. Steamed and sous vide artichoke exhibited the highest total phenolic content and total antioxidant capacity. Sous vide samples exhibited the highest concentrations of HMF, 2-furan-methanol and 2, 4-dihydroxy-2, 5-dimetyl-3(2H)-furanone, whereas the by-product 5-metylfuraldheide was only detected in the steamed product.